“Singkir Pageblug” Wayang Godhong the Cultural Power of Performing Arts During a Pandemic - Agus Purwantoro (Pusat Unggulan Ipteks Javanologi Universitas Sebelas Maret, 2023)
Since the COVID-19 pandemic hit the world, major and massive changes took place very quickly. Fortunately, the pandemic that is endemic throughout the world is offset by the technological advances of mankind, so there are many innovative solutions that we citizens of the world can adopt. One of the adaptive forms of humans in dealing with this pandemic is the mastery of virtual media (virtual/online world) which eventually becomes a new habit in running the wheel of life. The world of education is one of the sectors affected by the COVID-19 pandemic. In Indonesia, education which has to run online for more than a year has become an innovation for learning during the pandemic. However, the online learning process did not run optimally, in fact, it also resulted in a crisis for students at the An-Nawawi Wonosobo school. The wayang godhong art performance with the theme Singkir Pagebluk during the covid-19 pandemic is part of the movement or cultural power of the community in healing the crisis caused by COVID-19. This study uses a qualitative research method, which tries to reveal the crisis in school students during online learning and how wayang godhong can be a medium for the healing process due to the crisis experienced by students. In the world of art, like it or not, the performing arts of wayang godhong are challenged to create art by utilizing the mastery of virtual world technology in order to exist and survive. The analytical method used in the creation of the wayang godhong show entitled Singkir Pagebluk will explain (1) visualization of the Wayang Godhong show with students, (2) the process of wayang godhong performance as a cultural power to heal the crisis caused by the pandemic for students, (3) the direct impact felt by students from being involved in the performing arts of wayang godhong.